The Question of Providence and the Problem of Evil in Suhrawardī - Kaukua, Jari (Oriens, 2021)
Abstract Šihāb al-Dīn al-Suhrawardī’s philosophical works seem to contain two conflicting views on providence: in the Talwīḥāt and the Mašāriʿ, he endorses the Avicennian view, only to deny providence altogether in the Ḥikmat al-išrāq. This contribution aims to explain the seeming inconsistency by investigating it in light of the underlying question of God’s knowledge of particular things. I will also argue that despite his qualms concerning providence, Suhrawardī accepts the closely related Avicennian answer to the problem of evil.